From 3D to 2D zeolite catalytic materials - Přech, J; Pizarro, P; Serrano, D P; Čejka, J (Chemical Society reviews, 2018)
Research activities and recent developments in the area of three-dimensional zeolites and their two-dimensional analogues are reviewed. Zeolites are the most important industrial heterogeneous catalysts with numerous applications. However, they suffer from limited pore sizes not allowing penetration of sterically demanding molecules to their channel systems and to active sites. We briefly highlight here the synthesis, properties and catalytic potential of three-dimensional zeolites followed by a discussion of hierarchical zeolites combining micro- and mesoporosity. The final part is devoted to two-dimensional analogues developed recently. Novel bottom-up and top-down synthetic approaches for two-dimensional zeolites, their properties, and catalytic performances are thoroughly discussed in this review.